Particle Image Velocimetry A Practical Guide - Raffel, Markus; Willert, Christian E.; Wereley, Steven T.; Kompenhans, Jürgen (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This practical guide intends to provide comprehensive information on the PIV technique that in the past decade has gained significant popularity throughout engineering and scientific fields involving fluid mechanics. Relevant theoretical background information directly support the practical aspects associated with the planning, performance and understanding of experiments employing the PIV technique. The second edition includes extensive revisions taking into account significant progress on the technique as well as the continuously broadening range of possible applications which are illustrated by a multitude of examples. Among the new topics covered are high-speed imaging, three-component methods, advanced evaluation and post-processing techniques as well as microscopic PIV, the latter made possible by extending the group of authors by an internationally recognized expert. This book is primarily intended for engineers, scientists and students, who already have some basic knowledge of fluid mechanics and non-intrusive optical measurement techniques. It shall guide researchers and engineers to design and perform their experiment successfully without requiring them to first become specialists in the field. Nonetheless many of the basic properties of PIV are provided as they must be well understood before a correct interpretation of the results is possible.